2016
DOI: 10.1111/hepr.12812
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DQ gene polymorphisms are associated with hepatocellular carcinoma and hepatitis B surface antigen in chronic hepatitis B virus infection

Abstract: This study revealed an association between rs2856718 and HCC development and an association between rs7453920 and HBsAg levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Several SNPs associated with HCC have been reported and expression profiles generated [ 62 , 63 ]. These polymorphisms alter biological pathways, including inflammation, oxidative stress, DNA repair, cell cycle and growth factors [ 64 , 65 ]. The association between aflatoxin B1 and CHB is well established, and a concomitant SNP of GTSM1 (glutathione- S -transferase mu1) and GSTT1 (glutathione- S -transferase theta1) is associated with a dramatic increase in HCC risk [ 66 ].…”
Section: Genetic Risk Factors In Hepatocellular Carcinoma Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Several SNPs associated with HCC have been reported and expression profiles generated [ 62 , 63 ]. These polymorphisms alter biological pathways, including inflammation, oxidative stress, DNA repair, cell cycle and growth factors [ 64 , 65 ]. The association between aflatoxin B1 and CHB is well established, and a concomitant SNP of GTSM1 (glutathione- S -transferase mu1) and GSTT1 (glutathione- S -transferase theta1) is associated with a dramatic increase in HCC risk [ 66 ].…”
Section: Genetic Risk Factors In Hepatocellular Carcinoma Developmentmentioning
confidence: 99%
“…This indicates that the HCC risk attributable to specific polymorphisms depends on underlying risk factors and specific SNPs are associated with increased HCC risk in CHB. Such polymorphisms include SNPs of MDM2 (mouse double minute 2 homologue) and p53 [ 67 ]; XRCC3 (X-ray repair complementing defective repair in Chinese hamster cells 3) [ 68 ]; HLA (human leucocyte antigen)-DQ [ 64 ]; CTL-4 (cytotoxic T-lymphocyte antigen 4) [ 69 ]; GLB1 (galactosidase beta 1) [ 70 ] and TGF-β1 (transforming growth factor beta 1) but no other proinflammatory cytokines or interleukin-10 [ 71 ]. Nonetheless, these SNPs were mostly detected in collectives of CHB patients from the Far East or Asia and confirmatory studies in other patient populations are required.…”
Section: Genetic Risk Factors In Hepatocellular Carcinoma Developmentmentioning
confidence: 99%
“…Chronic HBV infection remains a serious global health problem [26,27]. It was reported that host genetic factors played an important role in the pathogenesis of HBV infection, and the polymorphisms of cytokine genes were strongly associated with the susceptibility to HBV infection in the general population [28,29]. ere is enough evidence that genetic variants of IFN-c signaling pathway genes play important roles in the HBV infection in adults [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, some single-nucleotide polymorphisms in several genes including HLA class I and II have been shown to be associated with HBV-related HCC. [16][17][18] It has been reported that NAs reduced HCC risk, but the effect is not adequate, especially in patients with advanced liver fibrosis. 6,[19][20][21] The HBV genomic sequences are heterogeneous, and based on differences of >8%, 22 10 genotypes (A to J) have been reported so far.…”
Section: H Epatitis B Virus (Hbv) Infection Is a Worldwidementioning
confidence: 99%
“…Recently, the hepatitis B X protein genotype was reported to be associated with HCC development and HCC proliferation in vitro and in vivo . Additionally, some single‐nucleotide polymorphisms in several genes including HLA class I and II have been shown to be associated with HBV‐related HCC . It has been reported that NAs reduced HCC risk, but the effect is not adequate, especially in patients with advanced liver fibrosis …”
Section: Introductionmentioning
confidence: 99%